Identification of a Missense Mutation in the FLNC Gene from a Chinese Family with Restrictive Cardiomyopathy [Letter] - Idrus HH (Journal of Multidisciplinary Healthcare)
Hasta Handayani Idrus1,2 1Department of Biomedical Sciences, Postgraduate School, Hasanuddin University (UNHAS), Makassar, Indonesia; 2Center for Biomedical Research, Research Organization for Health, National Research and Innovation Agency (BRIN), Cibinong Science Center, Cibinong-Bogor, West Java, IndonesiaCorrespondence: Hasta Handayani Idrus, Department of Biomedical Sciences, Postgraduate School, Hasanuddin University (UNHAS), Perintis Kemerdekaan Road KM.05, Makassar, South Sulawesi, Indonesia, Email hastahandayani99@gmail.com; hast006@brin.go.id